GEOLOGI DAERAH PANAS BUMI ULUBELU TANGGAMUS, LAMPUNG UTARA BERDASARKAN ANALISIS METODE MAGNETOTELLURIK (MT) - Panjaitan, Saultan (Pusat Survei Geologi, 2010)
Low resistivities of 0 – 15 Ώ m are interpreted as impermeable zones, functiming as cap rocks wich is hydrothermal alteration estimated to cinsist of clay. The midle resistivity 15 – 70 Ώ m is interpreted as permeable reservoir rocks located at 1250 – 2000 metres depth. The resistivity > 1000 Ώ m are metamorphic carbonate rocks. Block I in south of Mt.Rendingan and Block II at around Pagaralam hot spring formed up flow zone fluid reservoir having temperature of more than 260ºC, and contained 80 % vapour faction.Keywords: Geothermal,resistivity, impermeable, cap rock, hydrothermal alteration